Pengaruh Organizational Trust terhadap Kesiapan Individu untuk Menjalankan Perubahan Sistem Manajemen SDM di PT “X” Bandung - Indah Puspitasari (Humanitas (Jurnal Psikologi), 2018)
The aim of this study was to analyze the roles of organizational trust on the individual readiness for HR management system change at PT "X" Bandung. High level of individual readiness for change will increase the effectiveness of organizational change program. Population of this study was employees of PT "X" Bandung. Sampling was done by using purposive sampling technique with the criteria of being a permanent employee and having worked at least 1 year at PT “X”Bandung. A total of 100 respondents participated in this study. Data collection methods using individual readiness for change scale and organizational trust scale. Reliability score for individual readiness for is 0.919 and reliability score of organizational trust is 0.844. Simple linear regression analysis was used to test the hypotesis. Result indicated a significant effect organizational trust on the individual readiness for HR management system change at PT "X" Bandung. Data analysis showed that organizational trust play a role in improving individual readiness for changes (R2 = 0.085; p <0.05). This means that contribution of individual readiness changes is 8.5% and 91.5% is influenced by other factors not measured in this study.